Impact of Telematic Tutoring on the Teaching And Learning of Scientific Knowledge - Orbegoso Ciudad, Patricia Cecilia (Journal of Engineering Education Transformations, 2023)
: Tutoring acquires a special significance as it is designed, at least in theory, to facilitate autonomous learning with the accompaniment of the professor as a specialist in the disciplinary area. The objective of the study was to determine the impact of telematic tutoring on the teaching and learning process of scientific knowledge of engineering students at Alas Peruanas University in the city of Lima during the I lapse of 2020. Quantitative study of quasi-experimental design with pre- and post-test in a sample of 120 male and female students, all engineering students of Alas Peruanas University of Lima, Peru. The results determined a significant impact of telematic tutoring in the inquiry, experimentation and critical judgment skills; furthermore, it could be determined that students significantly increased their average performance after the intervention of the teacher as a telematic tutor in the teaching and learning process of scientific knowledge related to the engineering area. In conclusion, the use of telematic tutoring in the teaching and learning process in the engineering area has been shown to have a direct and significant impact on the scientific knowledge of university students.